THE PROCESS OF THE STRATEGIC MANAGEMENT MODEL FORMATION AND APPLICATION IN THE LITHUANIAN HEALTH CARE SYSTEM - Smilga, Edmundas; Janušonienė, Kristina (Ekonomika, 2009)
Today the ability to adapt to the constant and rapidly changing environment conditions is becoming the main factor of the success of the health care system Integration into the international area, globalization, and information processes in the society motivate to take strategic actions. Therefore, during the last decades the strategic management and more constructive application of its potential became the most important innovation in private and public sectors. In order to solve the strategic management problems the authors advise to create the model of the strategic management of the Lithuanian health care system. The analysis of the strategic management concept revealed that today the focus ist on the strategy implementation in the strategic management process. Successfully implemented strategy creates a competitive advantage for organizations. Therefore, the proper development of the strategic management process in health care system would have an impact on the development of health care system sector, as well as on the strategic management system of the whole Lithuanian economy. Then ultimate aim of the research is to form strategic management model of the Lithuanian health care system.. In the article the entire spectrum of methods of scientific and special research such as logical analysis and summarization of scientific material, systematic, comparative analysis was used. The structure of the article is the following: methodological assumptions are presented, and according to these assumptions Lithuanian health care system’s strategic management model is prepared and presented as well as reasons for the practical application of this model are presented. Scientific novelty, theoretical and practical significance of the research are the following – the strategic management model of the Lithuanian health care system, which is focused on the meeting of health needs of patients and potential clients, is prepared. The scientific results of the given article can also be used to develop the strategic actions for state and public institutions, which have an impact on the management of the health care system.